Indigenous Traditional Knowledge of Wild Medicinal Plants of Rupin Valley, Himachal Pradesh - Bhondge, Sunil Waman; Jishtu, Vaneet; Bhushan, Brij (Indian Forester, 2019)
Rupin valley is situated in remote region of Shimla district, Himachal Pradesh. The valley has a rich repository of medicinal and aromatic plants (MAPs). In the present investigation, an attempt has been made to explore the indigenous traditional knowledge (ITK) of medicinal plants and the healthcare system used for the betterment in the valley i.e. Dodra-Kwar Tehsil. In this study frequent field trips were made for the collection of the plant specimens as well as information on medicinal aspects from local healers and the elder people through questionnaire and interviews. The knowledge of medicinal plant, parts used, mode of administration and local name was also recorded with interviews. Ethnobotanical surveys were conducted across the different villages of Rupin valley during the year 2014 and 2015. The present study has resulted in the documentation of 55 different medicinal plant species belonging to 33 families and 46 genera.